The effect of orthodontic appliances on the Oral Candida colonisation: a systematic review - Campobasso Alessandra; Lo Muzio Eleonora; Battista Giovanni; Caponio Vito Carlo Alberto; Ciavarella Domenico; Lo Muzio Lorenzo (Sciendo, 2022)
To evaluate the influence of Fixed (FOA) and Removable Orthodontic Appliances (ROA) on oral Candida colonisation.